Citra Perempuan dalam Iklan Sabun Shinzui - Risman Iye; Susiati Susiati; Karim Karim (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Buton, 2020)
Advertising is a surefire tactic of producers in promoting an item or service so that interest and curiosity appear for consumers. This study aims to describe the characteristics of the image of women in Shinzui soap advertisements. This type of research uses qualitative methods with a semiotic approach. The data consists of two, namely primary data and secondary data. Data collection techniques in this research are observation and study of document contents. The data that has been obtained is then processed to look for the meaning contained in the data. The first thing to do is to write it in the form of a detailed description then reduce it (process it). The results showed that the three advertisements that became the research data have the same characteristics, namely in each scene the feminism traits have been shown, namely using a beautiful white dress, unraveling hair, a woman's posture that has purposional criteria and the image of women's figure is more highlighted in biological properties to attract consumers. Furthermore, the image of women in advertisements consists of two, namely having a biological or physical appeal and the attractiveness of gentle, graceful and graceful behaviors or characters.